2020
DOI: 10.3390/ani10030414
|View full text |Cite
|
Sign up to set email alerts
|

Reported Behavioural Differences between Geldings and Mares Challenge Sex-Driven Stereotypes in Ridden Equine Behaviour

Abstract: Horse trainers and riders may have preconceived ideas of horse temperament based solely on the sex of the horse. A study (n = 1233) of horse enthusiasts (75% of whom had more than 8 years of riding experience) revealed that riders prefer geldings over mares and stallions. While these data may reflect different sex preferences in horses used for sport, they may also reduce the chances of some horses reaching their performance potential. Further, an unfounded sex prejudice is likely to contribute to unconscious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
0
17
1
Order By: Relevance
“…However, their domestication has seen them deployed in transport, agriculture and military contexts [1], serving in roles they have occupied for centuries. Today, horses are found in various additional contexts, ranging from use in competition (e.g., racing and other performance sports), leisure riding and providing companionship [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, their domestication has seen them deployed in transport, agriculture and military contexts [1], serving in roles they have occupied for centuries. Today, horses are found in various additional contexts, ranging from use in competition (e.g., racing and other performance sports), leisure riding and providing companionship [2].…”
Section: Introductionmentioning
confidence: 99%
“…This will move from the current study, that is confined to prevalence and distribution at these anatomical locations, to risk factors for the various lesions reported here. It is expected that the follow-up study will explore the interactive role of multiple putative causal variables including: horse age; horse breed; horse sex; main equestrian disciplines (historic and current) as well as the 97 items of behavioural, management, and training data collected through the nascent Equine Behaviour Assessment Research Questionnaire (E-BARQ) instrument [21].…”
Section: Discussionmentioning
confidence: 99%
“…The results could also reflect differences in the way mares and geldings are handled. If mares are perceived as more difficult to train than geldings [ 23 ], this could lead to the use of detrimental training methods.…”
Section: Discussionmentioning
confidence: 99%
“…The horse’s behaviour under saddle is thought to be influenced by intrinsic factors, such as horse breed, sex, and age. While one recent study found that common equestrian preconceptions about the behaviour of mares were largely unfounded [ 23 ], a horse’s breed can influence its behaviour, temperament, and learning ability [ 24 , 25 ]. The behaviour of horses with multiple riders may also reflect common management flaws such as poorly fitting saddles and bridles [ 4 , 26 ], inappropriate diet [ 27 ], or untreated musculoskeletal pain [ 28 ].…”
Section: Introductionmentioning
confidence: 99%